ANALISIS FAKTOR KESULITAN BELAJAR SISWA PADA MATA PELAJARAN BIOLOGI KELAS X DI SMA PANCA BUDI MEDAN - Indah Purnama Sari Dalimunthe; Wina Dyah Puspita Sari (TUNAS : Jurnal Pendidikan Biologi, 2026)
This study aims to determine the level of learning difficulties and factors that cause students' learning difficulties in biology class X. Descriptive research with the type of qualitative and quantitative research. The sample of this study was taken by purposive sampling as many as 62 students under KKTP 75 (not yet completed). Data collection techniques used closed questionnaires, interviews and documentation. The results showed that class X experienced a level of learning difficulties in internal factors with an average of 53%, the category was quite influential, divided into health indicators with an average of 47% of the category was quite influential, and the psychological indicators averaged 59% of the category were quite influential. In external factors with an average of 44% of the category of less influential, divided into the average family indicator of 38% of the less influential category, the average school indicator of 40% of the category and the average community indicator of 55% of the category of quite influential and factors that affect physical condition and vision, interest, intelligence and motivation, parental attention, teaching methods and relationships between students and activities between communities, mass media and associations.